Peak functional ability and age at loss of ambulation in Duchenne muscular dystrophy. (14th February 2022) - Zambon, Alberto A.; Ayyar Gupta, Vandana; Ridout, Deborah; Manzur, Adnan Y.; Baranello, Giovanni; Trucco, Federica; Muntoni, Francesco; ,
Abstract : Aim: To correlate the North Star Ambulatory Assessment (NSAA) and timed rise from floor (TRF) recorded at age of expected peak with age at loss of ambulation (LOA) in Duchenne muscular dystrophy (DMD). Method: Male children with DMD enrolled in the UK North Start Network database were included according to the following criteria: follow‐up longer than 3 years, one NSAA record between 6 years and 7 years 6 months (baseline), at least one visit when older than 8 years. Data about corticosteroid treatment, LOA, genotype, NSAA, and TRF were analysed. Age at LOA among the different groups based on NSAA and TRF was determined by log‐rank tests. Cox proportional hazard models were used for multivariable analysis. Results: A total of 293 patients from 13 different centres were included. Mean (SD) age at first and last visit was 5 years 6 months (1 year 2 months) and 12 years 8 months (2 years 11 months) (median follow‐up 7 years 4 months). Higher NSAA and lower TRF at baseline were associated with older age at LOA ( p <0.001). Patients scoring NSAA 32 to 34 had a probability of 0.61 of being ambulant when older than 13 years compared with 0.34 for those scoring 26 to 31. In multivariable analysis, NSAA, TRF, and corticosteroid daily regimen (vs intermittent) were all independently associated with outcome ( p =0.01). Interpretation: Higher functional abilities at peak are associated with older age at LOA in DMD. This information is important for counselling families. These baseline measures should also be considered when designing clinical trials. Abstract : In Duchenne muscular dystrophy, we lack data linking early motor abilities to loss of ambulation (LOA). In this study, we investigated the relationship between two functional scores (i.e. North Star Ambulatory Assessment [NSAA] and Timed Rise from Floor [TRF]) recorded at the time of expected peak and LOA. Both higher NSAA scores and lower TRF were associated with later age at LOA. This information is important for counselling families and should also be considered when designing clinical trials.